Institutional Forces and Organizational Culture in China: Effects on Change Schemas, Firm Commitment and Job Satisfaction - Lau, Chung-Ming; Tse, David K.; Zhou, Nan (Journal of International Business Studies, 2002)
This paper examines the effects of institutional forces on change schemas of senior managers, mid-level managers and front-line workers of different types of firms in China. We postulate that several socio-economic forces including regional economic prosperity, firm type (state-owned and foreign-invested), within-firm ranks, and organizational cultures are at work. The cognitive differences among people in local and foreign firms operating in similar contexts are examined. Through a survey of 3,960 managers and workers we test hypotheses that relate various institutional forces on how individuals perceive, evaluate and infer future changes that challenge them. We also examine the effects of individual change schema on firm commitment and job satisfaction, two indicators that may mediate future changes in these firms.